2021
DOI: 10.1002/pds.5255
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain patients' willingness to share personal identifiers on the web for the linkage of medico‐administrative claims and patient‐reported data: The chronic pain treatment cohort

Abstract: Purpose: The linkage between patient-reported data and medico-administrative claims is of great interest for epidemiologic research. The goal of this study was to assess the willingness of people living with chronic pain to share personal identifiers on the web for the linkage of medico-administrative and patient-reported data.Methods: This methodological investigation was achieved in the context of the implementation of the chronic pain treatment (COPE) cohort. A web-based recruitment initiative targeting adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Data were collected with SurveyMonkey. A web-based recruitment strategy, which was shown as effective in previous studies, 37,38 was implemented to reach a community sample of Canadian living with CP. The questionnaire's hyperlink that led potential participants to the landing page of the study where enough information was provided for informed consent was included in the invitation message.…”
Section: Web-based Data Collectionmentioning
confidence: 99%
“…Data were collected with SurveyMonkey. A web-based recruitment strategy, which was shown as effective in previous studies, 37,38 was implemented to reach a community sample of Canadian living with CP. The questionnaire's hyperlink that led potential participants to the landing page of the study where enough information was provided for informed consent was included in the invitation message.…”
Section: Web-based Data Collectionmentioning
confidence: 99%
“…This retrospective study was conducted using data from the C hr O nic P ain tr E atment (COPE) Cohort ( 29 ), a dataset intended to better understand the real-world utilization of pharmacological, physical and psychological treatments among people living with CP. The COPE Cohort was implemented in the province of Quebec (Canada) and includes 1,935 adults living with CP who completed a web-based questionnaire between June and October 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported COPE data was also intended to be linked to longitudinal administrative data (medical and prescription claims). The complete methodology of the COPE Cohort implementation is described elsewhere ( 29 ). The study protocol was approved by the Université du Québec en Abitibi-Témiscamingue's research ethics committee and informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants living with chronic pain were recruited in a provincial web-based prospective cohort study examining pharmacological and nonpharmacological treatments used by adults living with chronic pain. 54 Additional information about the cohort study and recruitment procedures is shown in Figure 1. For this qualitative study, eligibility criteria included: (a) living with pain for at least 6 months, (b) using pharmacological pain treatments, and (c) experiencing one or more moderate to severe adverse effects.…”
Section: Design and Recruitmentmentioning
confidence: 99%